#Plugging Into Hope. (September 2021) - Fitzpatrick, Esther
This is a critical autoethnography of my "plugging into hope" through engagement with the Massive_Micro project as I was, literally and simultaneously, plugging into my computer during the COVID-19 pandemic isolation. In this article, I demonstrate the art of #plugging into hope. Through drawing on a range of visual, poetic, and narrative data generated throughout this project, I write my story, creating an assemblage of plugging in moments with human and non-human. Adding to an ongoing conversation with art-making, writing, and my scholarly ghosts. Highlighting the significance of deliberately plugging into embodied intra-action with our world/s—connecting to hope.